Acute resistance exercise performance is negatively impacted by prior aerobic endurance exercise - Ratamess, N. A.; Kang, J.; Porfido, T. M.; Ismaili, C. P.; Selamie, S. N.; Williams, B. D.; Kuper, J. D.; Bush, J. A.; Faigenbaum, A. D. (The Journal of Strength and Conditioning Research, 2016)
The purpose of the present study was to examine acute resistance exercise (RE) performance after 4 different aerobic endurance (AE) protocols. Eleven healthy, resistance-trained men (21.0 ± 1.2 years) performed a control RE protocol and 4 RE protocols 10 minutes after different AE protocols in random sequence. The RE protocol consisted of 5 exercises (high pull, squat, bench press, deadlift, and push press) performed for 3 sets of 6-10 repetitions with 70-80% of one repetition-maximum (1RM) with 3-minute rest intervals in between sets. The AE protocols consisted of treadmill running at velocities corresponding to: (a) 60% of their VO2 reserve (VO2R) for 45 minutes (P1); (b) 75% of their VO2R for 20 minutes (P2); (c) 90-100% of VO2R in 3-minute intervals (1:1 ratio) for 5 sets (P3); and (d) 75% of VO2R (4.5 mph) uphill (6-9% grade) for 20 minutes (P4). Completed repetitions, average power and velocity, heart rate (HR), and ratings of perceived exertion (RPE) were assessed each set. Protocols P1-P4 resulted in 9.1-18.6% fewer total repetitions performed compared with the control RE protocol with the squat experiencing the greatest reduction. Average power and velocity were significantly reduced for the high pull, squat, and bench press after most AE protocols. Ratings of perceived exertion values for the high pull and squat were significantly higher in P1-P4 compared with control. Heart rate was significantly higher during RE after P1-P4 compared with control by 4.3-5.5%. These results indicate acute RE performance is significantly compromised in healthy men after AE exercise of different type, intensity, and duration with largest reductions observed after high-intensity interval exercise.